2022
DOI: 10.1186/s41231-022-00128-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of peripheral blood cells allows to discriminate MIS-C and Kawasaki disease

Abstract: Background The pathogenesis of the novel described multisystem inflammatory syndrome in children (MIS-C) and Kawasaki disease (KD) is still debated as it is not clear if they are the same or different nosological entities. However, for both the diseases a rapid and unequivocal diagnosis is mandatory to start the therapy before the onset of severe complications. In this study, we aimed to evaluate the white cell populations in MIS-C and KD as potential markers to discriminate between the two dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…We speculate that IFN-γ has a main role in viral clearance. In all these 6 subjects, the flow-cytometry panel [41] resulted normal; furthermore, we analyzed a panel of 364 genes related to immunodeficiency [42], excluding any genetic alteration, and we did not find any correlation with age. At the state of the art, we are unable to define the cause of the lack of T-cell response after the vaccine.…”
Section: Discussionmentioning
confidence: 87%
“…We speculate that IFN-γ has a main role in viral clearance. In all these 6 subjects, the flow-cytometry panel [41] resulted normal; furthermore, we analyzed a panel of 364 genes related to immunodeficiency [42], excluding any genetic alteration, and we did not find any correlation with age. At the state of the art, we are unable to define the cause of the lack of T-cell response after the vaccine.…”
Section: Discussionmentioning
confidence: 87%
“…The difference is that the associated lymphocytopenia observed in patients with MIS-C has been compared to the significant neutrophilism and thrombocytosis observed in KD [4]. Other studies have found that the number of related lymphocytes observed in patients with MIS-C is decreased, while the number of neutrophils and platelets observed in KD is significantly increased [5]. In patients with MIS-C tested by deep immunoassay, a significant reduction of lymphocytes was found in a short period, while T cell involvement was more pronounced.…”
Section: Introductionmentioning
confidence: 95%